DEVELOPMENT OF MONOPOLY BOARD MEDIA ON THEME OF EVENTS IN LIFE CLASS V SDN MANDALAWANGI 2 - Desi Utari; Zerri Rahman Hakim; Damanhuri (Cakrawala Pedagogik, 2023)
This study aims to develop monopoly media on the theme of events in life and determine the feasibility of the developed media. In this study using the R&D research method on the Brog and Gall development design which has been modified by Sugiyono which includes 6 stages such as: 1) Problem analysis; 2) Data collection; 3) Product design; 4) Validation ah;I; 5) Design revision; 6) Product trials. This research was conducted in class V SDN Mandalawangi 2. Based on the feasibility results that had been carried out by a team of experts such as media experts, material experts and language experts. The results of research conducted by media experts obtained an average score of 89% in the "Very Eligible" category. The results of the validation by material experts obtained an average score of 88% in the "Very Eligible" category. And the validation results of linguists get an average score of 82% in the "Very Eligible" category. The results of the student response questionnaire in the limited trial obtained a score of 90% in the "Very Good" category. Based on the research results, the final product in the form of a monopoly board is suitable for use in learning activities in class V SD.